2005
DOI: 10.1007/s00020-005-1372-6
|View full text |Cite
|
Sign up to set email alerts
|

Linear-Fractional Composition Operators in Several Variables

Abstract: We investigate properties of linear-fractional composition operators Cϕ on Hardy and Bergman spaces of the ball in C N that are motivated by a formula for the self-commutator [C * ϕ , Cϕ]. In particular, we characterize when certain commutators [Cϕ, Cσ] are compact, and give conditions under which [T * z β , Cϕ] is compact, where T z β is multiplication by the monomial z β . Our results allow us to determine when Cϕ is essentially normal, for ϕ belonging to a large class of linear-fractional symbols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 20 publications
0
51
0
1
Order By: Relevance
“…A special case of Theorem 4 appears in [11], and the work in [11] has been extended in [5]. Our techiques here are different, and rely on an extension to several variables of the key geometric arguments of the last section, which we turn to next.…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…A special case of Theorem 4 appears in [11], and the work in [11] has been extended in [5]. Our techiques here are different, and rely on an extension to several variables of the key geometric arguments of the last section, which we turn to next.…”
Section: Theoremmentioning
confidence: 99%
“…Our starting point, in either the disk or the ball, will be the following necessary condition for compactness of C ϕ − C ψ . Theorem 1 [11,12]. Suppose ϕ, ψ are holomorphic self-maps of D (respectively, B N ) and suppose that there exists a sequence of points z n tending to the boundary of D (B N ) along which ρ(ϕ(z n ), ψ(z n )) 1 − |z n | 2 1 − |ϕ(z n )| 2 + 1 − |z n | 2 1 − |ψ(z n )| 2 (1) does not converge to zero, where ρ(ϕ(z n ), ψ(z n )) is defined by…”
Section: Introductionmentioning
confidence: 99%
“…The problem is subtle and no general answer is known. In this work, we have shown that the Berezin symbol of a bounded linear operator S from the Bergman space into itself satisfies certain averaging condition if and only if the operator S satisfy the intertwining relation C a SC a = S for all a ∈ D. Recently, the spectra of composition operators have attracted much attention (see [5][6][7]) from operator theorists. To this purpose, it is important to know what are the essential commutants of the invertible operators C a ,a ∈ D, and to characterize those…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present a necessary and sufficient condition for C a SC a − S = 0 to happen for all a ∈ D in terms of the Berezin symbol of S. Related work in this area can be found in [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…P. S. Bourdon, D. Levi, S. K. Narayan, and J. H. Shapiro in [3] have shown that a composition operator induced on H 2 by a linear-fractional self-map of the unit disk is nontrivially essentially normal if and only if it is induced by a parabolic non-automorphism. The essentially normal composition operators on other spaces have been investigated by some authors (see, e.g., [4], [12], and [13]). If ϕ and ψ are linear-fractional self-maps of D or B N , then C ϕ − C ψ cannot be non-trivially compact; i.e., if the difference is compact, either C ϕ and C ψ are individually compact or ϕ = ψ.…”
Section: Transformations That Take the Open Unit Disk D Into Itself Bmentioning
confidence: 99%